Dinoflagellate communities in high-risk Canadian Arctic ports. (5th March 2022) - Dhifallah, F.; Rochon, A.; Simard, N.; McKindsey, C.W.; Gosselin, M.; Howland, K.L.
Abstract: The expected increase of shipping activities in the Canadian Arctic is predicted to enhance potential introductions of non-indigenous species (NIS), including dinoflagellate taxa, which may have important ecological and economic impacts once released in a new environment. The lack of information about native species represents an obstacle in detecting the arrival of NIS. In this context, the present study characterizes dinoflagellate communities in high-risk Canadian Arctic ports to provide baseline data and to verify the presence of potential NIS and harmful taxa. In total, we identified 49 dinoflagellate taxa from 9 families in the ports of Churchill, Deception Bay, Iqaluit and Milne Inlet, including 7 taxa known to be potential toxin producers. Dinoflagellate communities differed significantly between ports and among time periods in the heavily used ports, those of Churchill (between 2007 and 2015) and Iqaluit (between 2015 and 2019). Comparisons between dinoflagellate communities in the ports and those in ballast water showed that 12 taxa found in ballast water of vessels discharging in Churchill and Deception Bay are potential NIS, confirming the introduction of new species by shipping activities. This may be exacerbated in the near future as a result of extended/prolonged ice-free conditions due to global warming. Highlights: Dinoflagellate communities differed significantly between the ports of Churchill, Deception Bay, Iqaluit and Milne Inlet and among years in Churchill and Iqaluit. Ice melt timing was a strong driver of community succession in the studied ports. Seven known potential toxin-producing species were identified in the ports, namely: Alexandrium cf. catenella, Dinophysis acuminata, Dinophysis acuta, Dinophysis norvegica, Gonyaulax spinifera, Phalacroma rotundatum and Protoceratium reticulatum. Comparisons between dinoflagellate communities in the ports and those in ballast water showed the presence of 12 potential non-indigenous species, confirming the introduction of new taxa by shipping activities.